OFR-16-74 Proceedings Of Thru-The-Earth Electromagnetics Workshop - Objectives And Constraints Of Through-The-Earth Electromagnetic Communication Systems - Howard E. Parkinson (The National Institute for Occupational Safety and Health (NIOSH), 1973)
In 1969, new coal mine health and safety legislation was enacted in the United States. As a result of this legislation, the Department of Interior, Bureau of Mines has carried out communications research aimed at developing whole mine communications for increased safety and efficient operation. The research has advanced and many promising results are now being demonstrated to the mining industry. However, there remains a challenge to further improve wireless communications within the mine workings and through the overburden above the workings. The objectives for future research and development will be discussed, together with the physical and operational constraints that new mine communication systems must face.